A retrospective analysis of speech and hearing in patients receiving surgery for submucous cleft palate. (February 2023) - Raby-Smith, Will; Hall, Per; Southby, Lucy; Parfect, Victoria; Linford, Georgina; Bannister, Sam; Miyagi, Kana
Summary: Submucous cleft palate (SMCP) is an uncommon subtype of cleft palate that is associated with symptoms of velopharyngeal insufficiency (VPI), the most common being hypernasal speech. A high proportion of patients also suffer from conductive hearing loss, which is thought to be due to eustachian tube dysfunction. A number of surgical techniques have been proposed to correct the anatomical defect that is responsible for VPI. This exploratory study aims to describe surgical techniques and clinical outcomes in a series of patients who underwent surgical repair of SMCP at a single regional specialist cleft centre between 1999 and 2018. Through a retrospective case note review, records of 57 patients who underwent SMCP repair between the ages of 6 months and 16 years were examined. Patients underwent one of the three surgical techniques: Intravelar Veloplasty, Furlow or a novel technique we have termed as "Hemi-Furlow". Hypernasality, measured on the Great Ormond Street Speech Assessment, showed evidence of improvement post-operatively in all three surgical groups ( P <0.005), with no evidence to favour any specific approach. Post-operative complications, including wound dehiscence and fistulae, occurred in nine patients (15.8%). Nine patients (15.8%) required revisional surgery, either due to post-operative complications or persistent speech problems. Otological disease was present in 54.4% of patients, comprising conductive hearing loss due to otitis media with effusion (52.6%) and sensorineural hearing loss (1.8%). There is now a need for large, multi-centre studies with robust outcomes measures to further examine relationships between surgical techniques and clinical outcomes in people born with SMCP.